Teaching relative clause to Bicolano learners of English - Alzaga, Carmen Arienda 1925- ([Quezon City publisher not identified], 1965)
This study presents materials for teaching relative clauses to Bicolano learners of English. The instructional materials have been prepared based on the results of a comparative analysis of English and Bicol relative clauses.
Thesis (Master in Education)--University of the Philippines.
Keywords: English language -- Study and teaching